Low-calorie diets and remission of type 2 diabetes in Chinese: phenotypic changes and individual variability - Zhenxiu Liu; Nannan Feng; Sujing Wang; Yang Liu; Jie Wang; Yue Tan; Ying Dong; Zhewei Sun; Xihao Du; Yaqing Xu; Feng Tao; Victor W. Zhong (Nutrition Journal)
Abstract Background Chinese have distinct phenotypes of type 2 diabetes (T2D) and obesity compared with people of other ethnicities, but using low-calorie diets to achieve T2D remission has never been conducted in Chinese. This study aimed to assess if T2D remission can be achieved using low-calorie formula diet (LCFD) and low-calorie real food-based diet (LCRFD) in Chinese similarly to other populations and to identify determinants of individual variability in T2D remission. Methods This 6-month intervention consisted of a 3-month isocaloric intensive weight loss phase (815–835 kcal/d) and a 3-month weight maintenance phase. Enrolled participants with T2D had BMI of 24–45 kg/m2 and HbA1c level of 6.5-12.0% (< 6.5% if on medication). Everyone stopped anti-diabetic drugs on day 1 and was assigned to receive LCFD (n = 21) or LCRFD (n = 20). Results At 6 months, 29.3% of participants had ≥ 12 kg weight loss, 39.0% lost ≥ 10% weight, and 56.1% achieved T2D remission. MRI-derived liver and pancreatic fat decreased significantly. Significant improvement was also seen in insulin sensitivity, continuous glucose monitoring-derived metrics, and various other cardiometabolic risk factors but not arginine-induced insulin secretory response. There was no difference in all outcomes between LCFD and LCRFD. Compared with responders for T2D remission, nonresponders were more likely to be women, and had more fat mass, longer diabetes duration, poorer glycemic control, and lower beta-cell function. Conclusions T2D remission rate and weight loss amount following low-calorie diet intervention in Chinese people were comparable to those reported from other populations, although individual variability existed. LCFD and LCRFD were similarly effective. Trial registration The trial was registered with ClinicalTrials.gov: NCT05472272.